THE RELATIONSHIP OF FAMILY SUPPORT WITH PATIENTS' SELF-EFFICACYTUBERCULOSIS MULTIDRUG RESISTANT (TB-MDR) AT POLY TB-MDR RSUD IBNU SINA GRESIK - Mar'atul Hasanah (Medical Studies and Health Journal (SEHAT), 2024)
Multidrug resistant (TB-MDR) occurs due to treatment failure, dropping, treatment, or improper treatment resulting in primary resistant. This research aimed to analyze the correlation between family support and self efficacy of multidrug resistant patient at TB-MDR Polly Ibnu Sina Hospital Gresik. Method : Descriptive correlational involved 15 respondents of TB-MDR patient who were undergoing treatment in poly TB-MDR of Ibnu Sina Gresik Hospital on 28 march – 28 june 2018 who were selected using consecutive sampling. Independent variable was family support. Dependent variable was self efficacy. Data were retrieved by questionnaire then analyzed using spearman rho with degree of meaning α ≤ 0,05. Result and analyze: Family support not significantly correlated with self efficacy with p-value = 0,120 or (p ≥ 0,05). Conclusion : All respondents of TB-MDR patients in TB-MDR Ibnu Sina Hospital Gresik have positive family support and high self efficacy. Suggestions for further researcher to research about health education to increase the participation of family support for TB-MDR patients.